The association between the dietary inflammatory index during pregnancy and risk of gestational diabetes: a prospective cohort study and a meta-analysis - Nastaran Payandeh; Hossein Shahinfar; Ahmad Jayedi; Majid Mirmohammadkhani; Alireza Emadi; Sakineh Shab-Bidar (BMC Endocrine Disorders)
Abstract Introduction To examine the association between dietary inflammatory index (DII) and risk of gestational diabetes mellitus (GDM). Methods A prospective birth cohort study was conducted in Iran. During the first trimester of pregnancy, food intake was measured using a food frequency questionnaire. Each participant’s DII score was calculated, and then, the Cox proportional hazard model was used to calculate the hazard ratio (HR) and 95% CI of GDM across the quartiles of DII. We systematically searched the literature to conduct a meta-analysis of observational studies (PROSPERO: CRD42022331703). To estimate the summary relative risk for the highest versus lowest category of DII, a random-effects meta-analysis was performed. The certainty of evidence was assessed using the GRADE approach. Results In the prospective cohort study (n = 635 pregnant mothers), the multivariable HRs of GDM for the third and fourth quartiles of DII were 2.98 (95%CI: 1.98, 6.46) and 2.72 (95%CI: 1.11, 6.63), respectively. Based on a meta-analysis of six prospective cohorts and a case-control study (1014 cases of GDM in 7027 pregnant mothers), being in the highest category of the DII was associated with a 27% higher risk of GDM (relative risk: 1.27, 95%CI: 1.01, 1.59; I2 = 50%; low certainty of evidence). A dose-response meta-analysis suggested a positive monotonic association between DII and GDM risk. Conclusions Our prospective cohort demonstrated a positive correlation between GDM risk and the inflammatory potential of diet in the first trimester of pregnancy. The results need to be confirmed by larger cohort studies. Clinical trial number Not applicable.